2012
DOI: 10.3846/16486897.2012.695734
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of heavy metals in sewage sludge and their removal using low-molecular-weight organic acids

Abstract: The total concentration and the concentrations of individual chemical species of selected heavy metals were estimated in primary and anaerobically digested sewage sludge. The concentration of Zn (1503 mg/kg) was highest and was followed by Cu (201 mg/kg), Cr (196 mg/kg), Pb (56 mg/kg), Ni (44 mg/kg) and Cd (3.6 mg/kg). The metal was divided into 5 fractions (exchangeable (F1), adsorbed (F2), organically bound (F3), bound to carbonates (F4), and residual (F5)) via sequential extraction. The sludge treatment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…The regression models were statistically significant for release of Mg, K, Al, Fe and Zn (R [17] reported that the heavy metal extraction efficiency increased with an increasing solution concentration. On the other hand, acid/sludge ratio had negative effect on the release of Fe, Zn and Al.…”
Section: Optimization Of Conditions For Release Of High Phosphorus Anmentioning
confidence: 98%
“…The regression models were statistically significant for release of Mg, K, Al, Fe and Zn (R [17] reported that the heavy metal extraction efficiency increased with an increasing solution concentration. On the other hand, acid/sludge ratio had negative effect on the release of Fe, Zn and Al.…”
Section: Optimization Of Conditions For Release Of High Phosphorus Anmentioning
confidence: 98%
“…EDTA and EDDS are strong chelating agents that form multidentate ligands with metal cations. It is expected that molecules with more carboxyl groups have higher extracting capacity than a molecule with fewer carboxyl groups [34], which could explain the higher efficiency for EDTA and CA (four and three carbonyl groups, respectively). However, this would suggest that EDDS (4 carbonyl groups) should behave similar to the EDTA, which is not the case (12 mg•kg −1 ).…”
Section: Batch Processmentioning
confidence: 99%
“…Thus, the integrated utilization of acids or reagents should be deliberately selected to fulfill the requirement of target contaminants removal on one hand, and soil ecological protection on the other hand. This justifies the introduction of Low molecular weight organic acids such as acetic acid, oxalic acid, which constitute a group of weak organic acids [63] and chelating reagents such as nitrilotriacetic acid (NTA) [33], sodium tripolyphosphates (STPP) and ethylenediaminetetraacetic acid (EDTA) [33,63]. The use of weak acids showed mitigated results even though promising.…”
Section: Chemical Leaching and Leaching Agentsmentioning
confidence: 99%